Information system development of an alternative raingauge network in rural areas. Case state Anzoategui, Venezuela - Orlando Olivares, Barlin; Cortez, Adriana; Rodríguez, María F.; Rey, Juan C.; Lobo, Deyanira (Acta Universitaria, 2016)
Knowledge of temporal changes in precipitation and its interaction with other components of the agricultural system facilitates agricultural planning, allowing better use of resources. The aim of this work was to develop an information system Network Alternative Pluviometers in rural areas of Anzoategui state. 22 Units of agricultural production plant located in different municipalities in the state were selected. Methodology of participatory action research and social intervention method was applied. Subsequently, network was integrated to the Information System of Agroecological Areas of the National Institute for Agricultural Research (INIA, by its Spanish acronym), providing opportunity to learn local characteristics of rain. The information system network aims to boost domestic development of communities where creation of new alternatives for use and management practices with ecological, economic and alternative approach makes possible, by strengthening capacity to innovate and disseminate technologies like based on planning in agriculture.
Keywords: Array; Array; Array